Comparison of competitive ELISA, indirect ELISA and agar-gel precipitation test for the detection of bluetongue virus antibodies in sheep - DAS, S C; MISHRA, S; MISHRA, N; K BHAGWAN, P S (The Indian Journal of Animal Sciences, 2013)
The present study was undertaken to compare 3 serological tests, viz. competitive enzyme linked immunosorbent assay(C-ELISA), indirect ELISA (I-ELISA) and agar-gell'recipitation test (AGPT) for detection of bluetongue virus (BTV) antibodies in sheep. Out of388 serum samples tested; AGPT could detect only 91 (23%), whereas ELISA could detect 247(63.6%) positive saplples. Testing of85 saplples by I-,ELISA and C-ELlSA showed that both the tests were more or less equally sensitive in detecting BTV antibo_dies. On analysing the breed distriblltion of positive samples tested by ELISA it was found that the Russian Merino, Bharat Merino, Rambouillet, Mutton cross, Avikalin and indigenous breeds of sheep had 92.8. 76.3, 73.07. 60.7, 61.4 and 53.6% of BTV antibodies respectively. The prevalence of higher rate of BTV antibodies in exotic breeds of sheep than crossbred and indigenous breeds showed their higher susceptibility of BTV. It was also found that the hoggets (85.7%) were more susceptible than the adults (62.4%) and both males and females were almost equally susceptible having per cent prevalance of 62.5 and 65.09 respectively.